Between Permanence and Adaptation: Transformations in Community Forest Management in Cherán, Michoacán - Piceno Hernández, Mónica (Ethnologies, 2021)
In the Purepecha community of Cherán (Mexico), forest management is carried out through a community government, a system recognized in the Mexican law, and obtained by Cherán after the 2011 uprising in response to the looting of forests by organized crime. In this context, indigenous traditions and daily forest use practices have changed. This study illustrates how Cherán confronted a socio-environmental crisis and is recovering its means of social reproduction. Specifically, it analyzes community institutions, gendered-power relations, and indigenous rights in the context of community-government relationship to discuss the importance of eco-territorial strategies beyond resistance. Grounded on ethnographic observations, interviews, and literature review, this article illustrates a community’s experience of building a path toward autonomous forest management. The case of Cherán provides insights into the development of autonomous community forest management as well as its objectives and relations with forest sustainability.